You've Got Quotes! - Frank, Russell (Quill)
Argues that interviewing through e-mail may fall short of other interview techniques. Limitations of e-mail interviews; Advantage of face-to-face interview; Why in-person interview is indispensable in profile writing; Best use of e-mail interview; Discussion on how the attribution of e-mail quotes should be handled. INSET: Say What?.